The impact of resistance training on gluteus maximus hypertrophy: a systematic review and meta-analysis - Krause Neto, Walter; Krause, Thaís Lima Vieira; Gama, Eliane Florencio (Frontiers in Physiology, 2025)
This systematic review aims to examine and synthesize the existing literature regarding gluteus maximus (GMax) hypertrophy as a result of dynamic exercises that incorporate hip extension with external resistance. A comprehensive search was undertaken across the following databases: PubMed/Medline, SportDiscuss, Scopus, Web of Science, CINAHL, Science Direct, Google Scholar, and ResearchGate. Twelve articles met the established inclusion criteria, leading to the subsequent key findings: 1) resistance training exhibits a moderate effect on GMax hypertrophy (11 studies, SMD 0.71, 95% CI [0.50, 0.91], p < 0.00001, I2 = 22%); 2) subgroup analyses of single (seven studies, SMD 0.74, 95% CI [0.36, 1.13], p = 0.0001, I2 = 52%) and combined (six studies, SMD 0.68, 95% CI [0.44, 0.92], p < 0.00001, I2 = 0%) training protocols have demonstrated moderate effects; 3) when emphasizing GMax hypertrophy at the expense of other muscle groups, single exercises, such as the barbell hip thrust, should be prioritized; 4) back squats performed in parallel or full range of motion significantly enhance GMax hypertrophy; 5) leg press machines and kneeling hip extensions can also facilitate increased GMax hypertrophy; 6) training programs that incorporate combined hip extension exercises, whether single-joint or multi-joint, significantly promote an increase in GMax hypertrophy. This study concludes that a variety of exercises—whether focused on a specific joint (single-joint) or encompassing multiple joints (multi-joint)—can effectively stimulate GMax hypertrophy, whether executed individually or in combination.